Florida 4-H Dairy Record Book - Karen Hamilton; Chris Decubellis; Chris Holcomb; Sarah Hensley (EDIS)
The Florida 4-H Dairy Record book is an animal sciences record book for all members in the dairy project to keep an accurate record of their project work. This is a major revision of Dairy and Dairy Goat Project Record Book.